“He is your son, but he isn´t yours” link, reciprocity and affection in Pablo Trapero´s “Leonera” - Merino Solari, Renatto Jorge (2021)
The article analyzes the film Leonera by Pablo Trapero. The film represents the story of Julia, a young and pregnant woman, who enters prison and must fight to achieve a space among the inmates, as well as defend the right to raise her child. From the ideas of bond and reciprocity, the way in which the protagonist constructs her social and affective interactions within the prison is explored. We conclude that Julia configured a complex network of exchanges (services, goods, affections, feelings and corporalities) that allowed her to give meaning to her experience in prison.